Flagships and tumbleweed: A history of the politics of gender justice work in Oxfam GB 1986–2015. (April 2018) - Crewe, Emma
This article contributes to scholarship on the political nature of feminists' work in international development NGOs. The case study of Oxfam GB (OGB) is contemporary history, based on compiling a brief history of gender justice work between 1986 and 2014 and 18 months of part-time participant-observation fieldwork during 2014–15. I describe funding pressures and imperatives, contestations of meaning and power struggles within OGB and argue that gender justice becomes entangled in both internal and the external politics of international development. This is part of a wider research programme about how ideas on gender equality norms travel between and around development organizations, so I finally draw conclusions about how norms are contested and embodied. The shapeshifting political nature of feminist work challenges prevailing theories about how norms and ideas travel and take hold within organizations.